Crohn's disease: NOD2, autophagy and ER stress converge. Issue 11 (19th January 2011) - Fritz, Teresa; Niederreiter, Lukas; Adolph, Timon; Blumberg, Richard S; Kaser, Arthur
Abstract : Polymorphisms in NOD2, encoding an intracellular pattern recognition receptor, contribute the largest fraction of genetic risk for Crohn's disease among the >40 risk loci identified so far. Autophagy plays a prominent role in the innate immune response towards intracellular bacteria. The discovery of the autophagy genes ATG16L1 and IRGM as risk factors for Crohn's disease turned autophagy into the spotlight in inflammatory bowel disease (IBD). Remarkably, NOD2 has recently been identified as a potent autophagy inducer. A physical interaction of NOD2 and ATG16L1 appears to be required for autophagic clearance of intracellular pathogens. Moreover, Crohn's disease-associated NOD2 and ATG16L1 variants exhibit a defect in the induction of an autophagic response and hence predict autophagy as a key converging mechanism that leads to Crohn's disease. Another pathway that is closely intertwined with autophagy and mutually cross-regulated is the unfolded protein response (UPR), which is induced by endoplasmic reticulum (ER) stress. Genes involved in the UPR ( XBP1, ORMDL3 ) have also been genetically associated with Crohn's disease and ulcerative colitis. Moreover, the intestinal epithelium at the interface between host and microbe appears particularly affected by IBD-associated hypomorphic function of autophagy and the UPR. The functional convergence of main genetic risk factors for IBD on these innate immune pathways has hence important implications for the host's interaction with the microbiota. Moreover, the genetic convergence on these molecular mechanisms may open novel therapeutic options for IBD that deserve further exploration.